Multi-Core Computer Vision and Image Processing for Intelligent Applications (ProtoView, 2016)
The nine contributions that make up the main body of the text are devoted to controlling prosthetic limb movements using EEG signals, parallel computing in face image retrieval, creating a sound glyph database for video subtitling, and a wide variety of other related subjects.